The Impact of Output Dinamics on Income Inequality in the Russian Regions - Vashchelyuk, Natalia Vasilievna (Economy of Regions, 2015)
According to the well-known theoretical approach (the Kuznets hypothesis), one should expect a rise in income inequality on the early stages of economic development followed by its decline on the later phases. But there are theoretical models, which suggest alternative paths of income disparity. Empirical evidences of different authors is also controversial. This paper analyses the relationship between income inequality and output in Russian regions. Such study, based on modern econometric techniques, is novel for Russia. The author uses different economic indicators for Russian regions and estimates the fixed effects model for the period from 2000 to 2011. The results indicate that there is a positive relationship between income inequality measured by Gini coefficient and real per capita gross regional product. Hence, the distribution of benefits of economic growth and losses due to economic contraction was unequal in this period. We decline of inequality was attributable to interregional migration processes, the rise in social expenditure and the ratio of employees with a higher level of education to the employees with a lower level of education. However, the increase in the share of firms implemented technological, management and marketing innovations caused the upswing in income disparity due to monopolistic effects. Wus, the statement of J. F. Kennedy that “a rising tide shifts all boats” is not suitable for the developments in Russian regions in 2000-2011.